2014
DOI: 10.1111/and.12312
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally induced hyperthyroidism influences oxidant and antioxidant status and impairs male gonadal functions in adult rats

Abstract: The objective of the present experiment was to study the effect of hyperthyroidism on male gonadal functions and oxidant/antioxidant biomarkers in testis of adult rats. Induction of hyperthyroidism by L-thyroxine (L-T4, 300 μg kg(-1) body weight) treatment once daily for 3 or 8 weeks caused a decrease in body weight gain as well as in absolute genital sex organs weight. The epididymal sperm counts and their motility were significantly decreased in a time-dependent manner following L-T4 treatment. Significant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 56 publications
(81 reference statements)
2
9
0
Order By: Relevance
“…Patients with hyperthyroidism usually notice a loss in their body weights, which is not consistent with observations in animal models of hyperthyroidism. Previous studies have observed a reduction [18], an increase [19, 20] or no change in body weight in hyperthyroid animals [21].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with hyperthyroidism usually notice a loss in their body weights, which is not consistent with observations in animal models of hyperthyroidism. Previous studies have observed a reduction [18], an increase [19, 20] or no change in body weight in hyperthyroid animals [21].…”
Section: Discussionmentioning
confidence: 99%
“…The elevated MDA level may be partly attributed to the high content of polyunsaturated fatty acids in the male germ cells membranes [ 13 ], thus rendering them particularly prone to lipid peroxidation. NO may cause spermatozoal dysfunction and infertility by inhibiting testicular T secretion, suppressing antioxidant enzyme activities [ 60 ] and generating peroxynitrite that is a more powerful oxidant [ 6 ]. GSH plays a pivotal role in the proliferation and differentiation of spermatogenic cells [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Group III: (hyperthyroid group), animals received L-T4 (300μg kg −1 , i.p.) dissolved in alkaline saline [ 6 ]. Group IV: (L-T4+DPP group), animals received DPP extract (150 mg kg −1 , p.o.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our main objective in this study was to investigate the arginine-NO pathway by measuring plasma total nitrite, arginase and Mn in hyperthyroidism. Although there are some studies dealing with NO levels, NOS activity and plasma concentration of asymmetric dimethylarginine, an endogenous inhibitor of NOS in the hyperthyroidism [1,[15][16][17][18][19], to our knowledge, this is the first report which has investigated arginase activity and Mn levels together with NO levels in hyperthyroidism.…”
Section: Introductionmentioning
confidence: 97%